Deodorization of Arthrospira platensis biomass for further scale‐up food applications. (2nd June 2017) - Cuellar‐Bermúdez, Sara P; Barba‐Davila, Bertha; Serna‐Saldivar, Sergio O; Parra‐Saldivar, Roberto; Rodriguez‐Rodriguez, José; Morales‐Davila, Sandra; Goiris, Koen; Muylaert, Koenraad; Chuck‐Hernández, Cristina
Abstract: BACKGROUND: Given the importance of A. platensis as a potential food protein source, we describe an affordable deodorization process that does not significantly affect the nutritional value of algae biomass. RESULTS: Ethanol, acetone or hexane were used to deodorize algae biomass and then to identify the profile of volatile compounds associated with its distinctive odor. Sensorial characteristics were improved in the biomass cake after the proposed solvent extraction. Panelists identified the ethanolic extract with the most pronounced algae‐related odor. Gas chromatography–mass spectrometry analysis showed that a mixture of 20 different compounds derived from fatty acids and amino acids contributed to the characteristic smell of A. platensis biomass . The results of the present study show that the ethanol solvent‐free A. platensis biomass contained > 600 g kg −1 protein, < 10 g kg −1 crude fat and > 65% in vitro protein digestibility, similar to the original biomass. The Fourier transform infrared spectroscopy secondary protein structure was comparable among samples, indicating that the only change after ethanol extraction was a reduction of the algae smell. CONCLUSION: The various extraction procedures investigated in the present study were effective in deodorizing the algae biomass. The most effective protocol was the removal of odoriferous compounds with ethanol. This particular procedure yielded an algae biomass with an improved sensorial traits. The results of the present study should help with the identification of odoriferous compounds derived from fatty acids, pigments and proteins associated with A. platensis . © 2017 Society of Chemical Industry